Low density of FOXP3-positive T cells in normal colonic mucosa is related to the presence of beta2-microglobulin mutations in Lynch syndrome-associated colorectal cancer - Echterdiek, Fabian Friedrich; Janikovits, Jonas; Staffa, Laura; Müller, Meike; Lahrmann, Bernd; Frühschütz, Monika; Hartog, Benjamin; Nelius, Nina; Benner, Axel; Tariverdian, Mirjam; Knebel Doeberitz, Magnus von; Grabe, Niels; et al. (OncoImmunology, 2016)
Microsatellite instability (MSI-H) is caused by DNA mismatch repair deficiency and occurs in 15% of colorectal cancers. MSI-H cancers generate highly immunogenic frameshift peptide (FSP) antigens, which elicit pronounced local immune responses. A subset of MSI-H colorectal cancers develops in frame of Lynch syndrome, which represents an ideal human model for studying the concept of immunoediting. Immunoediting describes how continuous anti-tumoral immune surveillance of the host eventually leads to the selection of tumor cells that escape immune cell recognition and destruction. Between 30 and 40% of Lynch syndrome-associated colorectal cancers display loss of HLA class I antigen expression as a result of Beta2-microglobulin (B2M) mutations. Whether B2M mutations result from immunoediting has been unknown. To address this question, we related B2M mutation status of Lynch syndrome-associated colorectal cancer specimens (n = 30) to CD3-positive, CD8-positive and FOXP3-positive T cell infiltration in both tumor and normal mucosa. No significant correlation between B2M mutations and immune cell infiltration was observed in tumor tissue. However, FOXP3-positive T cell infiltration was significantly lower in normal mucosa adjacent to B2M-mutant (mt) compared to B2M-wild type (wt) tumors (mean: 0.98% FOXP3-positive area/region of interest (ROI) in B2M-wt vs. 0.52% FOXP3-positive area/ROI in B2M-mt, p = 0.023). Our results suggest that in the absence of immune-suppressive regulatory T cells (Treg), the outgrowth of less immunogenic B2M-mt tumor cells is favored. This finding supports the immunoediting concept in human solid cancer development and indicates a critical role of the immune milieu in normal colonic mucosa for the course of disease.
Gesehen am 29.10.2024